1996
DOI: 10.1097/00005650-199607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Multiattribute Utility Function for a Comprehensive Health Status Classification System

Abstract: The Health Utilities Index Mark 2 (HUI:2) is a generic multiattribute, preference-based system for assessing health-related quality of life. Health Utilities Index Mark 2 consists of two components: a seven-attribute health status classification system and a scoring formula. The seven attributes are sensation, mobility, emotion, cognition, self-care, pain, and fertility. A random sample of general population parents were interviewed to determine cardinal preferences for the health states in the system. The hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
685
3
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 808 publications
(703 citation statements)
references
References 28 publications
8
685
3
7
Order By: Relevance
“…We measured 1 attribute of the HUI Mark 2 (HUI2) on Self‐Care. We used HUI decision tables to generate HUI2 and HUI3 single‐attribute utility scores22, 23 and applied coding algorithms to obtain overall HUI3 Health Index scores (see Supplementary Table 1C). 23 The latter represent the patient's state on a scale from 0 (equivalent to death) to 1 (equivalent to perfect health).…”
Section: Methodsmentioning
confidence: 99%
“…We measured 1 attribute of the HUI Mark 2 (HUI2) on Self‐Care. We used HUI decision tables to generate HUI2 and HUI3 single‐attribute utility scores22, 23 and applied coding algorithms to obtain overall HUI3 Health Index scores (see Supplementary Table 1C). 23 The latter represent the patient's state on a scale from 0 (equivalent to death) to 1 (equivalent to perfect health).…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of generic preference based instruments utilised in published studies between 2005 and 2010 identified the adult version of the EQ-5D as the most prevalent and widely used internationally, having been translated into 150 languages and applied in 63% of the studies identified (Richardson et al, 2014). Other popular generic preference based instruments applied internationally include the Short Form 6 Dimensions (SF-6D) (Brazier et al, 2002) and the Health Utilities Index (HUI) (Torrance et al, 1996). Whilst these instruments all differ in the way that they describe health and the number and type of included dimensions, they all comprise two common elements.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was originally developed for use in childhood cancer but has subsequently been used as a generic measure [32]. The HUI2 was developed from a review of epidemiological surveys and a review of the literature which generated a large pool of potential attributes.…”
Section: Hui2/hui3mentioning
confidence: 99%